The effect of the geomagnetic activity to the hourly variations of ionospheric foF2 values at low latitudes - Timocin, Erdinc; Yesil, Ali; Unal, Ibrahim (Springer Heidelberg, 2014)
In this study, the relationship between the hourly changes of the ionospheric critic frequency values of F2 layers in low latitudes and geomagnetic activity is examined by using statistical methods. The ionospheric critical frequency data has been taken from the Manila (121.1A degrees A E, 14.7A degrees A N) ionosonde station. In order to investigate the effect of sun activity on ionospheric critical frequency, the data of 1981 when the sun was active and of 1985 when the sun was less active has been used. According to the Granger causality test results, on 5 % significance level, a causality relationship from disturbance storm time (Dst) index values to ionospheric critical frequency values direction has been observed. However, a causality relationship from ionospheric critical frequency values to Dst values has not been observed. From the results of cause-and-effect analysis, it is evaluated that the effect of a shockwave occurring in geomagnetic activity on ionospheric critical frequency continues along 72 h, that is, geomagnetic activity has a long-term effect on ionospheric critical frequency. The response of ionospheric critical frequency to geomagnetic activity substantially depends on seasons. This response is more observed especially in equinox period when the sun is active and in winter months. The increase in geomagnetic activity causes ionospheric critical frequency to decrease in night hours and increase in day hours. The same relationship has not been observed exactly, though observed very little in winter months, for 1985 when the sun was less active.
Keywords: Ionospheric foF2; Dst index; Granger causality test; Impulse-response analysis; Time lagged regression